Implementasi Standart Kompetensi Penyuluh dalam Meningkatkan Kinerja Penyuluh Agama - Wanto, Wanto; Jannah, S. Fatiyathul; Yanto, Yanto; Sunandar, Dadan (STAI Publisistik Thawalib Jakarta, 2024)
This research aims to explore the importance of technical, managerial, and cultural competencies of religious counselors to enhance performance at the Office of Religious Affairs in Batumarmar Pamekasan. The role of counselors is crucial in effectively delivering religious teachings to a diverse audience with varying knowledge backgrounds and characteristics. This study adopts a descriptive research design with a qualitative approach. Data collection methods include observation, interviews, and documentation from key informants, primary informants (counselors), and supporting informants (counselors). The findings indicate that implementing technical competencies among religious counselors at the Office of Religious Affairs in Batumarmar Pamekasan aims to systematically and effectively improve their performance through deep understanding of Islamic teachings, effective communication skills, and counseling abilities. Creativity in teaching methods is essential for outreach to Muslim communities in rural and urban areas. Managerial competencies encompass activity planning, event organization, and evaluation of outreach programs to assess success. Leadership supports moral guidance, time management, and technological proficiency for task efficiency. Social-cultural competencies strengthen harmonious relations with diverse communities, promote tolerance, openness, and cultural values in religious duties.